Rules to be applied on publications Scientific Organization Of The United Nations Education, Science and Culture - UNESCO, CIUC (1962)
The Liaison Committee FID / ICSU / REL / OIN / Unesco, founded and gathered to discuss ways to conduct effective international action to improve the current state of scientific information, considers that the lack of discipline freely accepted on drafting and publication of scientific information is a major cause uselessly acrecen volume of documents issued, as well as costs for printing, summarize, classify and locate.